General characteristics, main virulence markers and new approaches in the control of helicobacter pylori - Camargo, Bruna Almeida Furquim de [UNESP]; Spósito, Larissa [UNESP]; Souza, Maurício Palmeira Chaves De [UNESP]; Ramos, Matheus Aparecido dos Santos [UNESP]; Fortunato, Giovanna Capaldi [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Taís Maria [UNESP] (My University, 2020)
Helicobacter pylori is classified as a Gram-negative, spiral and microaerophilic bacterium and considered one of the most common causes of gastric infections worldwide. It was isolated from gastric biopsy specimens from patients with chronic gastritis and peptic ulcers in 1983. Thereafter, H. pylori has been associated with other severe gastrointestinal tract diseases, such as chronic gastritis, mucosal lymphoma associated with gastric marginal zone, and gastric carcinoma. Besides, this bacterium is associated with extra-gastric diseases such as esophageal and colon diseases, biliary and liver diseases, neurological disorders, autoimmune and rheumatological disorders among others. H. pylori infections are estimated to affect around 50% of the world's population and, frequently has been linked to all the gastric cancer cases reported worldwide, thus constituting a public health problem.
Keywords: biofilm; Helicobacter pylori; nanotechnology; virulence markers